BANDWIDTH AND DURATION OF NONLINEAR-DISPERSIVE SIMILARITON - Zeytunyan, A. S. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2010)
Studying the spectral peculiarities of nonlinear-dispersive similariton, generated in single-mode optical fiber without gain (passive fiber), we reveal that the bandwidth of such a similariton is conditioned only by the initial pulse power. This property of nonlinear-dispersive similariton can be used for the pulse duration measurements at the femtosecond time scale, alternatively to the autocorrelation technique.
Keywords: fiber; femtosecond pulses; chirp; similariton